Preparing the mental motivation scale for Diyala University boxers - abd Al-Munaem, Firas (International Journal of Psychosocial Rehabilitation, 2020)
The attention in the sport psychological science began as an important science to achieve superiority in the sport performance, and it is in the front of other sciences to the success of the coach and to develop the sport performance. The importance lies in one of the important concepts in the human personality, and it is (the concept of the defensive tricks), and it is from the renewed concepts in psychology, science in general, and particularly in sport. This is the first study in local and on the Arabic level. The researchers did not find a study about this phenomenon and didn’t find a measure related to their current research and the environment in which they do the research. So the problem of research is stated in setting up a measure for the defensive tricks as it is one of the negative psychological features that needs a limited measure in the Iraqi environment that may help the Iraqi athlete to control the emotions and direct them to serve the performance and use the skilled physical abilities in a good way. This research is considered an important study for coaches and those who rule the university sport to put psychological and guiding programs that aim to reduce, modify, or rise any aspect from defensive aspects in the personality of their players.